Innocuous, Not Noxious, Input Activates PKCγ Interneurons of the Spinal Dorsal Horn via Myelinated Afferent Fibers - Neumann, Simona (Society for Neuroscience, 2008)
Protein kinase C γ (PKCγ), which is concentrated in interneurons of the inner part of lamina II of the dorsal horn, has been implicated in injury-induced allodynia, a condition wherein pain is produced by innocuous stimuli. Although it is generally assumed that these interneurons receive input from the nonpeptidergic, IB4-positive subset of nociceptors, the fact that PKCγ cells do not express Fos in response to noxious stimulation suggests otherwise. Here, we demonstrate that the terminal field of the nonpeptidergic population of nociceptors, in fact, lies dorsal to that of PKCγ interneurons. There was also no overlap between the PKCγ-expressing interneurons and the transganglionic tracer wheat germ agglutinin which, after sciatic nerve injection, labels all unmyelinated nociceptors. However, transganglionic transport of the β-subunit of cholera toxin, which marks the medium-diameter and large-diameter myelinated afferents that transmit non-noxious information, revealed extensive overlap with the layer of PKCγ interneurons. Furthermore, expression of a transneuronal tracer in myelinated afferents resulted in labeling of PKCγ interneurons. Light and electron microscopic double labeling further showed that the VGLUT1 subtype of vesicular glutamate transmitter, which is expressed in myelinated afferents, marks synapses that are presynaptic to the PKCγ interneurons. Finally, we demonstrate that a continuous non-noxious input, generated by walking on a rotarod, induces Fos in the PKCγ interneurons. These results establish that PKCγ interneurons are activated by myelinated afferents that respond to innocuous stimuli, which suggests that injury-induced mechanical allodynia is transmitted through a circuit that involves PKCγ interneurons and non-nociceptive, VGLUT1-expressing myelinated primary afferents.